PERILAKU MEROKOK ELEKTRIK (VAPING) PADA KOMUNITAS SEMARANG VAPE TRICKS - Dwi Lutfi Nugraheni; Priyadi Nugraha Prabamukti; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2019)
WHO states that Indonesia has the highest number of teenage smokers in the world. Various efforts have been made to reduce the tobacco epidemic, one of them is by switching to e-cigarettes. But in 2010, WHO no longer recommended its use as NRT because several studies found the substances that could be toxic and carcinogenic so that it was declared not to fulfill the safety factor. The phenomenon of electronic cigarettes is quite popular among young people, electronic cigarette used to be one of the alternative therapeutic media for conventional cigarette addicts, but now the function is shifted become a lifestyle and even an arena of achievement.The purpose of this study is to describe the behavior of electricity smoking (vaping) on Komunitas Semarang Vape Tricks. This study used qualitative method. The research subjects were 10 people who were obtained using purposive sampling method. Data collection was carried out through in-depth interviews. The results show that the subjects of the study have smoking history which is divided into 3 categories including beginners (never do conventional smoking), transition (from conventional cigarettes to electronic cigarettes) and dual users (electric cigarette users and conventional cigarette users as well). Almost all research subjects were accute smokers and long-time users of electronic cigarettes. it is suspected due to the lack of knowledge regarding the dangers of e-cigarettes, its negative attitudes and perceptions of e-cigarettes, the support of friends and family to use electronic cigarettes, the availability of electronic cigarettes and liquids, affordable price of electric cigarettes and liquids, and the existence of a legal status on e-cigarettes, in addition to the alleged sponsorship and endorsement of electronic cigarette brewers has contributions to the behavior of the research subjects in electricity smoking.